Pengaruh Video Tutorial Pembelajaran untuk Meningkatkan Hasil Belajar Pengetahuan Fungsi Bagian-bagian Mesin Las - Azmi, Muhammad Aldy Naufal; Khumaedi, Muhammad; Kriswanto, Kriswanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to determine the effectiveness of using video tutorial media in improving student learning outcomes on the material of welding machine parts functions at SMK IPT Karangpanas, Semarang. The research method used was a true experiment with a pretest-posttest control group design. The research sample consisted of 44 students of class X Machining Engineering who were randomly divided into an experimental group of 22 students and a control group of 22 students. The data collection instrument used was a multiple-choice objective test given before and after treatment. The experimental group received learning using video tutorials, while the control group followed conventional learning. The results of the independent sample t-test on the post-test showed a significant difference between the two groups (p < 0.001), with an average score of 85.23 for the experimental group and 68.86 for the control group. The normality and homogeneity tests met the requirements of parametric analysis. The results of the N-Gain analysis showed a high increase in the experimental group (0.7670) and a moderate increase in the control group (0.4741). These findings indicate that video tutorials are effective in improving students' conceptual understanding and technical skills and are suitable for use as an alternative learning strategy in vocational education.